Consumo de indumentárias de jovens alternativos na contemporaneidade - Camargo, Juliana Zemuner (2014)
While " fashion does not belong to all cultures and all ages " (Lipovetsky, 2009, p 24), since the dawn of time to dress is very significant in human relations. Although for some it does not pass a mere futility surface , a deeper analysis of this topic will reveal what the art of dressing is: the world of clothing is more than a simple act of dressing, but one of the ways most important to communicate and express what it is, or what you think, and the guy is like a monument carved and worked for him . " The body and clothing when building a united group of gestures aesthetic intention which is not restricted to the beauty, but a practice that form expressive artistic dimension " (PORTELA, 2010, p 4). In this sense, fashion meets demands of societies and social groups, and thus, in order to cater specifically to the subgroup designated as an alternative, in this postmodern society, intends to, through bibliographic methods, make a brief study of history of dress, habits of dress tied to human behavior, customs, symbols and ideology, in order to create a collection that respects diversity consistent with the subgroup in question. Thus, it is believed that this should support the preservation of existing tribes within the world of fashion, providing opportunities for the manifestation of being, as an individual or in a group, without mass or dictates of the products to be consumed.